2010
DOI: 10.21273/jashs.135.5.474
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Uptake and Partitioning of Macronutrients in Mature ‘Concord’ Grape

Abstract: Understanding how grape (Vitis L.) vines store nutrients in permanent tissues, how much nutrient vines take up from the soil, and how nutrients are partitioned and redistributed throughout the plant is critical to the development of sound nutrient management practices. This study investigated the seasonal patterns of macronutrient uptake and redistribution in whole ‘Concord’ grape (Vitis labruscana Bailey) vines. The study was conducted in a 42-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 10 publications
6
34
0
Order By: Relevance
“…A high level of internal recycling can be expected in the growing environment of this experiment in which movement of water below the root zone is minimal and gaseous N losses are small (Schellenberg et al, 2012). In many horticultural perennial crops, fruits have been identified as the greatest sink (Araujo and Williams, 1988;Alva et al, 2006;Cheng and Raba, 2009;Pradubsuk and Davenport, 2010;Roccuzzo et al, 2012). The percentage of tree nutrients partitioned to fruit in almond, however, is much greater than described for crops like apple (Cheng and Raba, 2009) and orange (Alva et al, 2006;Roccuzzo et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…A high level of internal recycling can be expected in the growing environment of this experiment in which movement of water below the root zone is minimal and gaseous N losses are small (Schellenberg et al, 2012). In many horticultural perennial crops, fruits have been identified as the greatest sink (Araujo and Williams, 1988;Alva et al, 2006;Cheng and Raba, 2009;Pradubsuk and Davenport, 2010;Roccuzzo et al, 2012). The percentage of tree nutrients partitioned to fruit in almond, however, is much greater than described for crops like apple (Cheng and Raba, 2009) and orange (Alva et al, 2006;Roccuzzo et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…The seasonal dynamics of nutrient contents shared a consistent pattern: translocation of nutrients from woody tissues to actively growing organs at the beginning of the season and nutrient movement to woody tissues occurring after veraison until leaf fall with no further nutrient uptake (Pradubsuk and Davenport 2010). Thus, in grapevines, as in other perennial species, N reserves accumulated in the previous seasons play a major role in growth after the winter CSIRO PUBLISHING Functional Plant Biology, 2015, 42, 105-114 phase (Lobit et al 2001;Zapata et al 2004).…”
Section: Introductionmentioning
confidence: 80%
“…Hanson and Howell (1995) found that 60% N uptake by established 'Concord' grapevines occurred between bloom and veraison. In a recent study conducted in an own-rooted 'Concord' single-curtain vineyard in Washington St, 90% to 95% N uptake occurred between bloom and harvest (Pradubsuk and Davenport, 2010).…”
Section: Changes In Soil Mineral Nitrogen During the Growing Seasonmentioning
confidence: 96%